2018
DOI: 10.1371/journal.pone.0196473
|View full text |Cite
|
Sign up to set email alerts
|

The chloroplast genome of Cerasus humilis: Genomic characterization and phylogenetic analysis

Abstract: Cerasus humilis is endemic to China and is a new fruit tree species with economic and environmental benefits, with potential developmental and utilization applications. We report the first complete chloroplast genome sequence of C. humilis. Its genome is 158,084 bp in size, and the overall GC content is 36.8%. An inverted repeats (IR) of 52,672 bp in size is separated by a large single-copy (LSC) region of 86,374 bp and a small single-copy (SSC) region of 19,038 bp. The chloroplast genome of C. humilis contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…For the location of FP, 240, 38, and 137 microsatellite loci were detected in the LSC, SSC, and IR regions, respectively. Similar patterns were also reported in other species, such as Cerasus humilis [ 36 ], Arabis stellari [ 40 ], and Paeonia ostii [ 41 ]. However, though the total number of microsatellites was highly conserved, polymorphisms might still be observed in certain loci, which could be helpful in population and evolutionary studies [ 42 , 43 , 44 ].…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…For the location of FP, 240, 38, and 137 microsatellite loci were detected in the LSC, SSC, and IR regions, respectively. Similar patterns were also reported in other species, such as Cerasus humilis [ 36 ], Arabis stellari [ 40 ], and Paeonia ostii [ 41 ]. However, though the total number of microsatellites was highly conserved, polymorphisms might still be observed in certain loci, which could be helpful in population and evolutionary studies [ 42 , 43 , 44 ].…”
Section: Resultssupporting
confidence: 85%
“…The trnH gene was located in the LSC region, and was shifted 1 bp to the right, compared with the other locations. These results showed that, with the species of Acer miaotaiense , the genomic structure was highly conserved, though genomic length variation can be found in the LSC and SSC boundary regions, as reported in other species [ 36 , 38 , 39 ].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Thus, we reported a high-quality chloroplast genome (cp) of P. dielsiana to lay the foundation in the genetic recognition and functional analysis. Comparative methods of inner or outer species in the same genus also provided a new promising approach for species natural and artificial evolution in genus Cerasus (Mu et al 2018).…”
mentioning
confidence: 99%
“…Thus, we reported the high-quality chloroplast genome of Prunus campanulata 'Fei han' to lay the foundation in the genetic recognition and functional analysis. The comparisons of related species in same genus also provided a verification for the application of super barcode in the cherry cultivars natural and artificial evolution in genus Cerasus (Mu et al 2018).…”
mentioning
confidence: 88%